Optimizing Urban Performance: Automated Multi-Objective Trade-offs Between Thermal Comfort and Energy Use in Hot Climates: Case study of Dubai City Walk. - Emam, Alaa (2025)
The growing challenge of urban heat stress in arid climates necessitates optimizing outdoor thermal comfort while reducing energy consumption. This study investigates the interplay between the Universal Thermal Climate Index (UTCI) and Energy Use Intensity (EUI) in an urban plot within Dubai City Walk. Using parametric modeling and multi-objective optimization, the research explores how urban morphology, building orientation, shading strategies, and ventilation corridors impact both pedestrian comfort and energy efficiency. The findings demonstrate that strategic urban configurations can reduce UTCI by up to 1.5°C and lower EUI by 26.5%, highlighting the potential of integrated design solutions to mitigate extreme heat. Seasonal analyses confirm the year-round effectiveness of optimized urban forms in improving outdoor usability while minimizing cooling loads. By bridging the gap between outdoor thermal performance and energy demand, this study offers practical insights for urban planners and policymakers to develop climate-responsive and energy-efficient urban environments. The results align with sustainability objectives, underscoring the need for adaptive design approaches to enhance livability in hot regions. Keywords: outdoor thermal comfort, energy use intensity (EUI), universal thermal climate index (UTCI), urban morphology, passive cooling, hot climates, sustainable urban design.